ANALYSIS OF INVESTOR BEHAVIOR IN THE ETHICAL REVIEW OF SHARIA ECONOMIC LAW - Mubarok, Anas Bayan; Nurjaman, Muhamad Izazi (AT-TIJARAH: Jurnal Penelitian Keuangan dan Perbankan Syariah, 2024)
This research aims to analyze investor behavior in reviewing the ethics of sharia economic law. This research includes library research using descriptive analytical research methods with a qualitative approach. The data analysis technique is carried out in three stages, namely data reduction, data presentation and conclusions. The results of this research reveal that in securities trading on the Sharia Capital Market it is still possible for behavior or actions to occur that violate professional ethics and existing rules. The two main actors who play a role in securities trading practices in the Sharia Capital Market are the behavior of issuers and investors. There are several deviant activities in securities trading practices in the Sharia Capital Market, namely: first, Fraud, this fraudulent act can include the behavior of Misleading information, Pooling interest, and Alternate trade. Second, market manipulation, including the practice of: Wash sale, Pre-arrange trade, Pump and Dump, Hype and Dump, Creting fake demand/supply), Cornering, and Marking at the close. Third, the use of insiders can be in the form of insider trading and front running. Some of these investors' behavior is not in accordance with the ethics of the sharia economics profession which can lead to unhealthy sharia capital market business behavior.